Caring for patients near the end-of-life at Mayo Clinic: A narrative - Ingram, Cory (The International Journal of Whole Person Care)

(untitled) (McGill University Library, 2022)
I’m a palliative care and hospice doctor focusing my clinical care on families near the end of life.  It has been a great privilege to be welcomed to the bedside of so many seriously ill and dying patients to care for them and their families. Pursuing geriatrics and palliative care were not always met with welcome sentiments from my peers. “You’re going to take care of sick and dying patients.” “It is so depressing.” My experience is that geriatrics and palliative care are a little like peeking through the old skeletal keyhole into a living room.  You have to get up real close to peek inside and if you dare to go through and enter in, a whole new world opens. It is often a sacred space.  A space for a team of professionals caring together.